Endurance sport events in Switzerland: An examination of the competition characteristics that define the ideal event from the Swiss participant`s perspective and clarify their motivators for event participation - Steingruber, R. (graubünden Trailrun, 2022)
Previous studies examining motivations to participate in an endurance sports event have primarily focused on perceptions and characteristics of the participant him/herself or characteristics relating to the event. However, they overlooked participants desired competition characteristics of an event: (1) number of different sport types; (2) respective sport types; (3) event duration; (4) length of distance; (5) evaluation form; (6) social form and (7) event format. To fil the void, the aim of this study was to investigate the characteristics that define the ideal endurance sports event from the Swiss participants point of view and clarifying their motivators for event attendance. The empirical research was conducted through 13 expert interviews with interviewees from various event organisations to gain insight into the endurance sports event industry. Followed by an online survey, completed by 385 Swiss individuals with experience in participating in endurance sport events in Switzerland, to investigate the competition characteristics and motivational factors. A focus group, as well as three expert talks for deeper interpretation and better understanding of the results, concluded the research. The results of the study showed that the ideal endurance sports event consist of one up to three sport types, which are mainly road run, trail run, mountain bike or road bike. Event duration is between half a day and a whole day, the race distance is medium, evaluation form is a ranking list according to time. Participants want to complete the event as a single athlete and in the classical race format. Most important motivation motives to participate in an event are challenge, experience / fun, comparison with self and others, as well as motivation for training. The results from this study provide endurance sport event organisations in Switzerland with current expectations and perceptions of participants about their ideal competition characteristics, including motivations to participate in events.